Class trip to the Cave of Doom - McMullan, Kate.; Basso, Bill (New York : Grosset & Dunlap, 1998)
Wiglaf joins the other students of Dragon Slayers$1 (BAcademy in searching the Dark Forest for the Cave of Doom, which supposedly contains the gold of the dead dragon Seetha.s
Keywords: Dragons -- Fiction; Buried treasure -- Fiction; Caves -- Fiction; Schools -- Fiction